2021
DOI: 10.1016/j.virusres.2021.198464
|View full text |Cite
|
Sign up to set email alerts
|

Immune characterization and profiles of SARS-CoV-2 infected patients reveals potential host therapeutic targets and SARS-CoV-2 oncogenesis mechanism

Abstract: The spread of SARS-CoV-2 and the increasing mortality rates of COVID-19 create an urgent need for treatments, which are currently lacking. Although vaccines have been approved by the FDA for emergency use in the U.S., patients will continue to require pharmacologic intervention to reduce morbidity and mortality as vaccine availability remains limited. The rise of new variants makes the development of therapeutic strategies even more crucial to combat the current pandemic and future outbreaks. Evidence from sev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Despite the controversial debate about the oncogenic (or oncolytic) potential of SARS-CoV-2, several genes with a role in oncogenesis have been found regulated upon its infection, such as those corresponding to E2F transcription factors and pRB, thus suggesting a putative mechanism for SARS-CoV-2 in contributing to oncogenesis through the potential inhibition of oncosuppressors [84]. Interactomics studies were pivotal to obtaining such mechanistic insights [85].…”
Section: The Oncogenic Potential Of Sars-cov-2mentioning
confidence: 99%
“…Despite the controversial debate about the oncogenic (or oncolytic) potential of SARS-CoV-2, several genes with a role in oncogenesis have been found regulated upon its infection, such as those corresponding to E2F transcription factors and pRB, thus suggesting a putative mechanism for SARS-CoV-2 in contributing to oncogenesis through the potential inhibition of oncosuppressors [84]. Interactomics studies were pivotal to obtaining such mechanistic insights [85].…”
Section: The Oncogenic Potential Of Sars-cov-2mentioning
confidence: 99%
“…On the other hand, mutations of these repair genes seem to drive oncogenesis [38]. In this respect, certain identified genes, including E2F transcription factors and retinoblastoma tumor-suppressor gene (RB1), modulated by COVID-19 infection, appear to be involved in SARS-CoV-2-related carcinogenesis [39]; genetic variants of IL12RB1 confer genetic susceptibility to SARS-CoV-2 infection [40]; and mutations to RB1 and/or components regulating the cyclin dependent kinase-RB-E2F signaling pathway have been recognized in almost every human cancer [41]. In this setting, mutations in genes (hMSHS2, hMLS1, hPMS1, hPMS2) that also control the DNA mismatch repair process have been involved in oncogenesis.…”
Section: Immunity After Sars-cov-2 Infection Versus Post Vaccinationmentioning
confidence: 99%
“…The question of the potential oncogenic role of SARS-COV-2 remains unclear and will only be answered over time. Policard et al (2021) identified genes modulated by COVID-19 infection implicated in oncogenesis, including E2F transcription factors and RB1; this finding suggests a mechanism by which SARS-CoV-2 infection may contribute to oncogenesis [33] . Such observations has not yet been validated in the clinical setting.…”
Section: Sars-cov-2 and Cancer Interactionsmentioning
confidence: 99%